(untitled) (Studia Prawnicze / The Legal Studies, 2023)
In this article basic legal and social problems connected with the access to justice are discussed, for the category of population of Mexico which the Author names the „underpriviledged”. Analising the evolution of Mexican legislation, opinions presented in the legal doctrine as well as the results of empirical studies, the Author presents the shortcomings of Mexican civil procedure as far as protection of underpriviledged is concerned. The Author stresses the fact that Mexican civil procedure stays behind brisk socio-economic changes which took place in this country. The civil procedure based on traditional principle of free exercise by the parties of their rights does not allow for the court’s activity aimed at finding out objective truth. According to the Author’s opinion proceedings before the court constitute a „bastion of liberal capitalism” in which „all cases are adjudicated taking into account contractual freedom of the parties”. Thus; they create no effective mechanism of adjudicating typical cases resulting from new structure of socio-economic relations. While analising the data gathered in results of empirical studies, the Author stresses the fact that „legal aid” for the poor” is only an illusion. First of all, these persons rarely turn to the courts seeking protection of their rights. Also the length and the costs of proceedings in civil law suits are very disadvantageous to them as well as negative effect of such proceedings in most cases. This corroborates an opinion widely spread among the poorer groups of Mexican population that „justice is only for the rich”.